Traditions of Yoga in Existential Posthuman Praxis - Banerji, Debashish (Journal of Posthumanism, 2021)
This is a discussion of Francesca Ferrandoâ€™s book Philosophical Posthumanism, focusing in particular on three chapters, â€œAntihumanism and the Ubermensch,â€ â€œTechnologies of the Self as Posthumanist (Re)Sourcesâ€ and â€œPosthumanist Perspectivism.â€ It traces the origins and implications of the concepts at the center of these chapters from a posthumanist perspective. It then evaluates these implications from the viewpoint of a non-Western praxis, specifically the spiritual praxis of Indian yoga. For this, it elaborates briefly on some genealogies of yoga and discusses what an intersection of posthumanism and yoga may look like. It holds that such a consideration would enhance the concepts of the chapters in question in Ferrandoâ€™s text.